2020
DOI: 10.3389/fnbeh.2020.00047
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and Compulsivity After Subthalamic Deep Brain Stimulation for Parkinson’s Disease

Abstract: Impulsivity and compulsivity are prominent non-motor problems in Parkinson's disease (PD). Despite 20 years of research, there is still an ongoing debate as to whether subthalamic deep brain stimulation (STN DBS) for PD exacerbates or improves these symptoms. Here, we review how STN DBS affects clinical symptoms and neurocognitive aspects of impulsivity and compulsivity. When comparing patients post-to pre-surgery, in the majority of studies STN DBS for PD is associated with a decrease in clinically diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 76 publications
0
14
1
1
Order By: Relevance
“…Consistent with previous studies, we did not find an effect of the preoperative motor score (UPDRS-III) on postoperative ICB changes. 8 Moreover, we found that lower LEDD-DA was a predictor for greater improvement in QUIP-RS total score. A possible explanation might be that patients with higher tendency to develop ICB, may be unable to tolerate higher doses of DA, 36 37 perhaps prompting surgical evaluation.…”
Section: Motor Symptoms and Dopaminergic Medicationmentioning
confidence: 66%
“…Consistent with previous studies, we did not find an effect of the preoperative motor score (UPDRS-III) on postoperative ICB changes. 8 Moreover, we found that lower LEDD-DA was a predictor for greater improvement in QUIP-RS total score. A possible explanation might be that patients with higher tendency to develop ICB, may be unable to tolerate higher doses of DA, 36 37 perhaps prompting surgical evaluation.…”
Section: Motor Symptoms and Dopaminergic Medicationmentioning
confidence: 66%
“…The hypothesis that ventral STN might be dedicated to cognitive functions and dorsal STN to motor functions ( Jahanshahi et al., 2015 ) stems from the observation that prefrontal cortical areas project to the former, whereas motor and premotor cortices project to the latter ( Haynes and Haber, 2013 ). This observation has been corroborated by the effects on DBS outcome of the location of the target stimulation in the dorsoventral/occipitorostral axis of the STN ( Greenhouse et al., 2013 ; Scherrer et al., 2020 ; van Wouwe et al., 2017 , 2020 ).…”
Section: Deep Brain Stimulation Beyond Motor Control: Mood and Decisi...mentioning
confidence: 64%
“…Retrospektywne badania prowadzone w małych grupach chorych dawały szeroki zakres rezultatów -od poprawy objawów z kręgu ICD po implantacji systemu DBS, poprzez brak wpływu zabiegu DBS-STN, po pogorszenie lub rozwój ICD de novo (Kim et al, 2013). W ostatnich latach opublikowano jednak wiele prospektywnych badań randomizowanych wskazujących na korzystne oddziaływanie DBS-STN na zmniejszenie objawów ICD (Scherrer et al, 2020). Jeszcze mniej jasny wydaje się wpływ na rozwój ICD implantacji DBS do części wewnętrznej gałki bladej (internal globus pallidus, DBS-GPi), aczkolwiek w nielicznych opublikowanych do tej pory doniesieniach obserwowano tylko pojedyncze przypadki rozwoju tego schorzenia po wszczepieniu DBS-GPi (Moum et al, 2012).…”
Section: Epidemiologia I Czynniki Ryzykaunclassified